Interrupted Game of England and French Huguenots on the Chessboard - ASHRAFYAN, KONSTANTIN E.; KOROLEVA, NATALYA E.; POSPELOVA, NADEZHDA V.; ACHAEVA, MARINA S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The investigation is about the christianization of Florida in 16th-17th centuries. A chain of events took place in different parts of the world: Spanish Florida, west-India, England, France, Spain, and Italy. We analyzed the actions of France, and England during the Religion Wars in Europe, and their preparation which were connected with wishes of Frenchmen and English to reach Spanish Florida and close the path of the Spanish ships route. Also, we show the intelligence activities of England to identify routes for further capturation of parts of modern North America and establish its protectorate. RESUMEN La investigación trata sobre la cristianización de Florida en los siglos XVI-XVII. Una cadena de eventos tuvo lugar en diferentes partes del mundo: La Florida española, oeste de India, Inglaterra, Francia, España, e Italia. Analizamos las acciones de Francia, e Inglaterra durante las Guerras de Religión en Europa, y su preparación, las cuales estaban conectadas con los deseos de franceses e ingleses de llegar a la Florida española y cerrar los caminos de la ruta de los barcos españoles. Además, mostramos las actividades de inteligencia de Inglaterra para identificar rutas para una mayor captura de partes de la moderna América del Norte y establecer su protectorado.